Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2x - 23. 33 = 138
2x - 8 . 27 = 138
2x - 216 = 138
2x = 138 + 216
2x = 354
2x = 354 : 2
x = 177
vậy x = 177
( 6x - 34 ) . 73 = 3 . 74
( 6x - 81 ) . 343 = 3 . 2401
( 6x - 81 ) . 343 = 7203
6x - 81 = 7203 : 343
6x - 81 = 21
6x = 21 + 81
6x = 102
x = 102 : 6
x = 17
vậy x = 17
\(2x-2^3.3^2=138\)
\(2x-8.9=138\)
\(2x-72=138\)
\(2x=138+72\)
\(2x=210\)
\(x=210:2\)
\(x=105\)
\(\left(6x-3^4\right).7^3=3.7^4\)
\(\left(6x-3^4\right)=3.7^4:7^3\)
\(\left(6x-3^4\right)=3.7\)
\(6x-81=21\)
\(6x=21+81\)
\(6x=102\)
\(x=102:6\)
\(x=17\)
\(27+\left(220-6x\right).3=615\)
\(\rightarrow\left(220-6x\right).3=615-27=588\)
\(\rightarrow220-6x=588:3=196\)
\(\rightarrow6x=220-196=24\)
\(\rightarrow x=24:6=4\)
\(315-\left(x-3\right).7=210\)
\(\Rightarrow\left(x-3\right).7=315-210=105\)
\(\Rightarrow x-3=105:7=15\)
\(\Rightarrow x=15+3=18\)
a)4.(x+3)-(2x-12)=x-(-11+4)
4x+12-2x+12=x+11-4
2x+24=x+7
2x-x=-24+7
x=-17
b)-(4x-13)+(5x-4)=-3-(-15+7)
-4x+13+5x-4=-3+15-7
(-4x+5x)+13-4=12-7
x+9=5
x=-4
c)(5x-3)-(-2x+4)=6x-12
5x-3+2x-4=6x-12
5x+2x-6x=3+4-12
x=-5
d)(15x+20)-(9x-3)=5x-(-12)
15x+20-9x+3=5x+12
15x-9x-5x=-20-3+12
x=-11
e,(7x+14)+(3x-8)=-(-9x+3)
7x+14+3x-8=9x-3
7x+3x-9x=-14+8-3
x=-9
\(\left(6x-3^4\right).7^{13}=3.7^{14}\)
\(\left(6x-3^4\right).7^{13}=3.7.7^{13}\)
\(\Rightarrow6x-81=21\)
\(\Rightarrow6x=102\)
\(\Rightarrow x=17\)